ANTHROPOLOGIST ANA HILDA RAMÍREZ CONTRERAS (1961-2021) - Ortíz Elizondo, Héctor (Universidade de Brasília, 2021)
Tribute to Anthropologist Ana Hilda Ramírez Contreras (1961-2021), prepared by Héctor Ortíz Elizondo representing the Latin American Network of Legal Anthropology (Relaju), Mexico.